Incidental Findings in POCUS: "Chance favors the prepared mind" - Sara Obeid; Benjamin Galen; Trevor Jensen (CINQUILL Medical Publishers Inc., 2022)
Point of Care Ultrasound (POCUS) has the potential to rapidly aide in diagnostic algorithms at the bedside, however POCUS users are often faced with the dilemma of appropriate management of incidental findings [1]. Incidental findings in POCUS are defined as any indeterminate, benign, or potentially concerning finding found unexpectedly that is not related to the patient's chief complaint [2]. Increased use of POCUS has driven the increased discovery of incidental findings, with a reported frequency between 1.6% to 26% depending on the institution, frequency of documentation, and level of experience [1,2]. While many incidental findings are benign, some are not and benefit from follow-up. This raises important concerns regarding the need for systematic, evidence-based guidelines to ensure necessary follow-up while avoiding unnecessary additional imaging, patient anxiety and increased healthcare costs [1,3].